2021
DOI: 10.1097/rli.0000000000000840
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hypersensitivity Reactions to Iopromide in Children and Elderly

Abstract: The aim of this study was to analyze the risk of hypersensitivity reactions (HSRs) to iopromide in children and elderly patients in comparison to adults. Materials and Methods: Four observational studies were pooled and analyzed (analysis I). In addition, spontaneous reports from 1985 to 2020 from the pharmacovigilance database were evaluated (analysis II). All patients received iopromide for angiographic procedures or contrast-enhanced computed tomography in various indications. In analysis I, a nested case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The scanning parameters of CT were as follows: section thickness 5.0 mm, tube voltage 120 kV, tube current 220 mA. Iopromide injection [ 21 ] (300 mg/mL) was rapidly injected through the patient’s elbow vein with a high-pressure syringe at a flow rate of 2 mL/s at a dose of 1.5 mL/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
“…The scanning parameters of CT were as follows: section thickness 5.0 mm, tube voltage 120 kV, tube current 220 mA. Iopromide injection [ 21 ] (300 mg/mL) was rapidly injected through the patient’s elbow vein with a high-pressure syringe at a flow rate of 2 mL/s at a dose of 1.5 mL/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
“…In all studies, the population was considered homogenous concerning gender, which bespeaks the important role of these compounds in medical practice for all patients. However, two recent studies performed by Endrikat et al demonstrated a higher risk of iopromide hypersensitivity reactions in adults, particularly when administered via the intravenous route, when compared with children and older individuals [31]. Still, other studies have reported conflicting results regarding the relationship between age and ARs [27,28].…”
Section: Iopromide Adverse Events Assessmentmentioning
confidence: 99%
“…The safety profile of iopromide has been characterised through extensive studies reporting the ARs, possibly by applying it to the databases records. Regardless the vast clinical experience with contrast media, including iopromide, many safety issues still need elucidation [31]. Despite being described as safe with rare serious ARs, ICM use can be potentially severe and even lethal [25,32,33].…”
Section: Iopromide Adverse Events Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incidence of ADRs in elderly patients is not always higher than that in non-elderly adults. Endrikat et al 120 found that the risk of hypersensitivity reactions in patients older than 65 years after iopromide administration was lower than that in non-elderly adults as identified by analysis of the data in four observational studies and the PV database. Gouverneur et al 121 found no more or more severe ADRs with the use of drugs targeting metastatic colorectal cancer (mCRC) in elderly patients in their analysis of ICSRs in VigiBase.…”
Section: Elderly Patientsmentioning
confidence: 99%